The scholarly publishing landscape of ethnobotany in the Philippines - Magsayo, Venice Nicole; Pulmones, Joselle; Ca, Nyanha Caira; Fiel, Chastine Hazel; Kwong, Kyra Alexa; Sanchez, Febie Anne; Bacharo, Kurt Bryant (Ethnobotany Research and Applications, 2024)
Background: Ethnobotany deals with the investigation on the interaction and inter-relationship between plants and human societies. Owing to the research priorities in finding new drugs, conserving plant biodiversity, and documentation of vanishing indigenous cultures, bibliometric analysis on ethnobotany had been conducted in various countries to assess its research productivity. This bibliometric analysis purposively summarizes the current scholarly publishing state of ethnobotany in the Philippines. Methods: All published primary articles on ethnobotany that has been conducted in the Philippines from 2001 to 2022 and available in Google Scholar were retrieved, screened, and analyzed using three bibliometric indicators namely quantity, performance, and structural. Results: A total of 163 articles has been retrieved related to Philippine ethnobotany published in 106 journals. The journal Biodiversitas was shown to have the highest number of articles published (4.91%) while the Journal of Ethnopharmacology was the most cited. Contributors included 370 authors and co-authors affiliated to more than 100 local and foreign institutions. Of these, G.J. Alejandro was identified as the most prolific author (18 articles, 343 citations) while the University of Santo Tomas was the most productive institution (22 articles). International collaboration revealed that Filipino researchers collaborated with 13 different institutions located in seven countries. In terms of funding, only less than half of the total articles examined (46.01%) declared to received financial support. The main research theme in the entire study period centered around medicinal plants while the most recent focused on the different indigenous communities in Mindanao Island and the field of ethnophycology. Conclusions: Despite these developments, potential predatory publishing practices and parachute science are documented. The former can threaten the quality and credibility of research outputs whereas the latter can be exacerbated when local scientists and Indigenous Peoples are not empowered to participate in the scholarly process. Moving forward, we call for the participation of current and future researchers in the field of Philippine ethnobotany and all fields to raise the bar of scholarly publishing high. Carrying the best practices should be adopted across all publishing landscape. Keywords: Bibliometric Analysis, Scientometrics, Google Scholar, Ethnobotany, Philippines